Technical approach for the inclusion of superconducting magnetic energy storage in a smart city. (1st September 2018) - Colmenar-Santos, Antonio; Molina-Ibáñez, Enrique-Luis; Rosales-Asensio, Enrique; López-Rey, África
Abstract: Smart grids are a concept which is evolving quickly with the implementation of renewable energies and concepts such as Distributed Generation (DG) and micro-grids. Energy storage systems play a very important role in smart grids. The characteristics of smart cities enhance the use of high power density storage systems, such as SMES systems. Because of this, we studied the possibility of adapting these systems in this kind of electrical topology by simulating the effects of an energy storage system with high power density (as SMES). An electrical and control adaptation circuit for storing energy was designed. The circuit consisted of three blocks. The first one was a passive filter LCL. The second was a converter system that allows rectifying of the signal when the system runs in charge mode but acts as an inverter when it changes to discharge mode. Finally, there is a chopper that allows the current levels to be modified. Throughout simulations, we have seen the possibility of controlling the energy supply so as the storage. This permits to adapt to different contingencies which may induce the wiring of the charge in the net, as well as different types of charges. Despite the technical contribution of this kind of systems in the Spanish electrical network, there are big obstacles that would prevent its inclusion in the network, such as the high cost of manufacturing and maintenance compared with other cheaper systems such as superconductors or the low energy density, which limits their use. Graphical abstract: Image Highlights: Development of a theoretical SMES system and simulation of parameters. EESS systems with high power density can be used to eliminate signal fluctuations. Smart cities might contribute to the energy quality improvement in industrial areas. Possibility of inclusion of SMES systems through hybrid systems.